Incentive effects from write-down CoCo bonds: An empirical analysis - Henning Hesse (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
Departing from the principle of absolute priority, CoCo bonds are particularly exposed to bank losses despite not having ownership rights. This paper shows the link between adverse CoCo design and their yields, confirming the existence of market monitoring in designated bail-in debt. Specifically, focusing on the write-down feature as loss absorption mechanism in CoCo debt, I do find a yield premium on this feature relative to equity-conversion CoCo bonds as predicted by theoretical models. Moreover, and consistent with theories on moral hazard, I find this premium to be largest when existing incentives for opportunistic behavior are largest, while this premium is non-existent if moral hazard is perceived to be small. The findings show that write-down CoCo bonds introduce a moral hazard problem in the banks. At the same time, they support the idea of CoCo investors acting as monitors, which is a prerequisite for a meaningful role of CoCo debt in banks' regulatory capital mix.
urn:nbn:de:hebis:30:3-466786
Keywords: G18; G21; G32; 330; CoCo bonds; contingent capital; endogenous risk; capital structure; incentives; monitoring